2016
DOI: 10.1097/phm.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Proprioceptive Exercises in Patients with Subacromial Impingement Syndrome

Abstract: Although proprioceptive exercises may provide better proprioceptive acuity, no additional positive effect on other clinical parameters was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 42 publications
3
95
1
2
Order By: Relevance
“…Both Dilek et al (2015) and Naughton et al (2005) found the JPS improved after exercise training in the patients with shoulder impingement syndrome and patients with shoulder posterior dislocation. Therefore, because chronic pain and effusion may influence JPS centrally and peripherally (Röijezon et al, 2015), by reducing pain and decreasing symptoms with exercises (Littlewood, Ashton, Chance-Larsen, May, & Sturrock, 2012), JPS may be restored in patients with shoulder injuries.…”
Section: Discussionmentioning
confidence: 97%
“…Both Dilek et al (2015) and Naughton et al (2005) found the JPS improved after exercise training in the patients with shoulder impingement syndrome and patients with shoulder posterior dislocation. Therefore, because chronic pain and effusion may influence JPS centrally and peripherally (Röijezon et al, 2015), by reducing pain and decreasing symptoms with exercises (Littlewood, Ashton, Chance-Larsen, May, & Sturrock, 2012), JPS may be restored in patients with shoulder injuries.…”
Section: Discussionmentioning
confidence: 97%
“…Measured before and after intervention.Pain:VASROM: GoniometerStrength: Hand held dynamometerFunction and QoL: WORC.Clinical tests: Joint Position Sense and Lateral Scapular Slide TestPatients outcomes improved statistically in both groups ( P  < 0.05).No significant difference between groups in all parameters ( P  > 0.05) except muscle strength for lower trapezius and supraspinatus and clinical tests ( P  < 0.05).Comments: Missing P -values and CI in results section. No protocol registered.Low risk:RandomizationDrop-out rateIntention-to-treatUnclear risk:AllocationComplianceHigh risk:Other bias (sample size)High risk (downgrade 1)ModerateDilek 2016 [57]Randomized using block randomization. n = 63, 21 male, 42 women. 25 – 65 years.…”
Section: Resultsmentioning
confidence: 99%
“…For crossover trials only data from the first period were included [53]. The outcomes measures of pain during movement and function were found comparable across five studies [53–57]. The function scoring scales were reversed in two studies [55, 57] for the adequate interpretation and to enable meta-analysis of the data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The results in our study are similar to those reported in the treatment with proprioceptive exercises and conventional physiotherapy. 40 …”
Section: Discussionmentioning
confidence: 99%